Social Influence and Digital Payment Adoption among Generation Z: The Mediating Role of Lifestyle - Ferry Panjaitan; Krismanto Erick Tobush Naibaho; Romindo Megawati Pasaribu; Hanna M Damanik; Jeremy William Siahaan (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: The expansion of financial technology has accelerated digital payment usage, particularly among Generation Z, who exhibit strong digital engagement and online consumption. This study investigates the influence of influencers and electronic word-of-mouth (e-WOM) on the adoption of digital payments, with lifestyle as a mediating variable. Research Methodology: A quantitative approach was employed through a structured survey of 200 Generation Z respondents in Medan City, who actively use fintech services, including e-wallets and other digital payment applications. Data were analyzed using Partial Least Squares structural equation modeling (PLS-SEM) with SmartPLS 3.3 to evaluate measurement validity and structural relationships. Results: The findings demonstrate that influencers and e-WOM have positive and significant effects on digital payment adoption. Lifestyle also plays a significant mediating role, indicating that social media exposure shapes digital-oriented consumption patterns that encourage fintech usage. Conclusions: Digital payment adoption among Generation Z is influenced not only by technological convenience but also by socially driven lifestyle factors formed through online interactions. Limitations: The study is limited to respondents from a single city and relies on self-reported data, which may restrict broader generalizations. Contributions: This study enriches the digital payment adoption literature by integrating lifestyle as a mediating construct between social influence and fintech usage, offering practical implications for fintech providers in developing targeted digital communication strategies.